Protective effect of rhaponticin on ovariectomy‐induced osteoporosis in rats. Issue 9 (5th July 2021) - Yang, Tiansong; Wang, Qingyong; Qu, Yuanyuan; Feng, Chuwen; Li, Chaoran; Yang, Yan; Sun, Zhongren; Alahmadi, Tahani A.; Alharbi, Sulaiman A.; Bao, Shengyong
Abstract: Rhaponticin is a constituent isolated from numerous medicinal herbs. It has been reported earlier that rhaponticin possesses numerous biological effects like antiallergic, antidiabetic, hepatoprotective, and antithrombosis. The goal of this exploration was to scrutinize the therapeutic potential of rhaponticin on ovariectomy (OVX)‐triggered osteoporosis in rats. Female Sprague Dawley rats were arbitrarily allocated to a sham‐operated control group I, group II, which underwent OVX, and groups III and IV that underwent OVX were administered with rhaponticin (10 and 20 mg/kg). Rhaponticin was supplemented orally after 4 weeks of OVX and continued for about 16 weeks. Our findings exhibit that rhaponticin prevented the BMD diminution of femurs, induced by OVX, and protected the worsening of trabecular microarchitecture that are assisted through a noteworthy decline in skeletal remodeling as noticed through the diminished status of bone markers in a dose‐dependent manner (10 and 20 mg/kg). OVX rats treated with rhaponticin efficiently enhanced body weight, lipid profiles, uterine index, bone turnover markers, inflammatory markers, and augmented the incidence of calcium in the OVX rats. Rhaponticin was established to restrain the functions of acid phosphatase, estradiol, and bone gla protein in OVX rats. Also, rhaponticin displayed some beneficial effects on histomorphometric and histopathological examination. It was observed that tabular area and thickness were reinstated in sham control and rhaponticin‐treated OVX rats. We recognized that rhaponticin did not induce a damaging outcome on the skeletal organization of OVX rats. Moreover, we denote that rhaponticin can be an exceptional agent for the treatment and deal with associated bone diseases.